1999
DOI: 10.1073/pnas.96.19.10911
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A activates locus coeruleus cell firing and increases arousal in the rat

Abstract: The localization of orexin neuropeptides in the lateral hypothalamus has focused interest on their role in ingestion. The orexigenic neurones in the lateral hypothalamus, however, project widely in the brain, and thus the physiological role of orexins is likely to be complex. Here we describe an investigation of the action of orexin A in modulating the arousal state of rats by using a combination of tissue localization and electrophysiological and behavioral techniques. We show that the brain region receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
784
5
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,103 publications
(860 citation statements)
references
References 19 publications
49
784
5
7
Order By: Relevance
“…Orexin-A has been previously reported to increase the activity of LC cells following direct application to brainstem slices and iontophoretic application directly onto LC cells (Hagan et al, 1999;Bourgin et al, 2000;Murai and Akaike, 2005) and SB-334867 has been shown to block these effects (Soffin et al, 2002). The present study confirms and extends these findings by showing that i.c.v.…”
Section: Discussionsupporting
confidence: 87%
“…Orexin-A has been previously reported to increase the activity of LC cells following direct application to brainstem slices and iontophoretic application directly onto LC cells (Hagan et al, 1999;Bourgin et al, 2000;Murai and Akaike, 2005) and SB-334867 has been shown to block these effects (Soffin et al, 2002). The present study confirms and extends these findings by showing that i.c.v.…”
Section: Discussionsupporting
confidence: 87%
“…Obesity is generally believed to reflect decreased metabolic activity and energy expenditure in hypocretin deficient animals, an effect that would be quantitatively more important than hypophagia. Interestingly, intracerebroventricular injection of hypocretin has potent stimulatory effects on sympathetic outflow (Samson et al, 1999;Shirasaka et al 1999) and cortisol release but decreases prolactin and growth hormone release (Hagan et al 1999). Central administration of hypocretin-1 was also shown to increase metabolic rate (Lubkin and Stricker-Krongrad 1998).…”
Section: Food Intake Energy Metabolism and Neurohormonal Control Ofmentioning
confidence: 99%
“…This finding was followed by the observation that hypocretin knockout mice have sleep and behavioral abnormalities reminiscent of narcolepsy (Chemelli et al 1999). Other studies have indicated dense projections to all monoaminergic cell groups and wake-promoting effects of hypocretins when administered centrally (Hagan et al 1999). More recently, clinical studies have shown that most patients with narcolepsy have undetectable hypocretins in the CSF and a striking decrease in hypocretin immunoreactivity and transcript levels in the perifornical hypothalamus Thannickal et al 2000).…”
mentioning
confidence: 94%
“…Orexin (also known as hypocretin) is a neuropeptide that has been reported to play a role in the regulation of feeding, drinking, body temperature, general activity (Lubkin and Stricker-Krongrad, 1998;Edwards et al, 1999;Hagan et al, 1999;Kunii et al, 1999;Mondal et al, 1999;Piper et al, 2000;Estabrooke et al, 2001;Hungs et al, 2001;Yoshimichi et al, 2001;Kotz et al, 2002;Berthoud et al, 2005), energy homeostasis (Mintz et al, 2001), stimulation of gastric secretion in rats (Takahashi et al, 1999), increasing metabolic rate in rats (Lubkin and Stricker-Krongard, 1998), altering luteinising hormone release in rats (Pu et al, 1998) and in the regulation of the sleepwake cycle specifically associated with increased wakefulness and inhibition of REM sleep (Sakurai et al, 1998;Chemelli et al, 1999;Siegel, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Thannickal et al, 2000;van den Pol, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of orexin-immunopositive (Orx +) cell bodies and terminal networks within the brain has been reported in a range of mammals including: humans (Homo sapiens, Moore et al, 2001); domestic cat (Felis catus, Zhang et al, 2001Zhang et al, , 2002; domestic sheep (Ovis aries, Iqbal et al, 2001); six species of rodent (laboratory rat, Rattus norvegicus -Broberger et al, 1998;Peyron et al, 1998;Chen et al, 1999;Cutler et al, 1999;Date et al, 1999;Hagan et al, 1999;Nambu et al, 1999, Risold et al, 1999Baldo et al, 2003;Chou et al, 2004;Espana et al, 2005;Kirouac et al, 2005;Nixon and Smale, 2007; Nile grass rat, Arvicanthus niloticus - Novak and Albers, 2002;Nixon and Smale, 2007;golden or Syrian hamster, Mesocricetus auratus -McGranaghan and Piggens, 2001;Mintz et al, 2001;Vidal et al, 2005;Nixon and Smale, 2007; laboratory mouse, Mus musculus, C57B1 strain, Broberger et al, 1998;Siberian or Djungarian hamster, Phodopus sungorus -McGranaghan and Piggins, 2001;Khorooshi and Klingenspor, 2005;degu, Octodon degus -Nixon and Smale, 2007); five microchiropteran species (Kruger et al, 2010); and the Eastern grey kangaroo (Macropus giganteus, Yamamoto et al, 2006). The Orx + neuronal cell bodies were invariably localized within the hypothalamus and while for most mammals they were represented as a rather homogenous loosely packed large cluster of neurons located in the perifornical and lateral hypothalamus (see above references), in certain rodents there may be up to four clusters, or nuclei, of orexinergic neurons -the two described above, plus one cluster located in the anterior hypothalamic paraventricular subnucleus and one in the lateral ventral hypothalamic supraoptic area (LVHA) (Nixon and Smale, 2007).…”
Section: Introductionmentioning
confidence: 99%